The Relationship between Antenatal Care (ANC) Compliance with Pregnancy Risk Detection - Rancakasari, Ayu Ditya; Kasiati, Klanting; Setiyani, Astuti; Susilaningrum, Rekawati (JURNAL KEBIDANAN, 2025)
Increased risk factors during pregnancy are caused by the failure of pregnant women to comply with pregnancy checks. This study aims to identify compliance with ANC visit frequency, identify compliance with iron tablet consumption, identify compliance with calcium consumption, identify pregnancy risk detection, analyze the relationship between ANC visit compliance and pregnancy risk detection, analyze the relationship between compliance with iron tablet consumption with pregnancy risk detection, and analyze the relationship Compliance with calcium consumption and detection of pregnancy risk. This type of research uses analytical observational through a cross sectional approach. The population in this study was 156 people and the research sample was 113 people using purposive sampling. The results of research from 113 respondents, according on the Chi Square test, showed that there was a relationship between compliance with ANC visits and detection of pregnancy risk (0.022 α), there was a relationship between compliance with consuming iron tablets and detection of pregnancy risk (0.024 α), and there was a relationship between compliance with calcium consumption and detection of pregnancy risk (0.013 α). According on the description above, it is concluded that there is a relationship between compliance with ANC visits and the detection of pregnancy risk, compliance with the consumption of iron tablets with the detection of the risk of pregnancy, and there is a relationship between compliance with calcium consumption also the detection of the risk of pregnancy. The suggestions for institutions are used as a reference for knowledge and information, for health services can be used to conduct health education, and for pregnant women can be used as learning to be aware of pregnancy risks.